Bill Nye the science guy's great big book of science, featuring oceans and dinosaurs - Nye, Bill (Hyperion, 2005)
Contains two books. The first describes the ocean and its life forms and suggests related activities to help understand marine biology. The second presents information on over thirty different dinosaurs and includes experiments.